Chiral Lewis Acid Catalysis in Water - Ogawa, Chikako; Kobayashi, Shu (Current Organic Synthesis, 2011)
The progress of development in chiral Lewis acid catalyzed reaction in water is described. Lewis acid surfactant-combined catalyst and chiral bipyridine ligand complex realized catalytic asymmetric hydroxymethylation and ring-opening reaction in water successfully. Furthermore, silica-supported Lewis acid catalyst was applied for asymmetric hydroxylation in water.
Keywords: asymmetric